History of the Graeco-Latin fable - Adrados, Francisco Rodríguez, 1922- (Mnemosyne, Supplements, 1999)
This third volume of the History of the Graeco-Latin Fable offers a complete inventory and documentation of the Classical fable tradition in Antiquity and the Middle Ages. The original Spanish edition (1987) has been considerably enlarged with numerous supplementary references and less than 350 new fables. The present edition uniquely refers to fables in more than 20 different languages, not only in Greek and Latin, but also in other Oriental and Western languages such as Sumerian, Assyrian, Babylonian, Sanskrit, Egyptian, Syriac, Arabic, Hebrew, Turkish, Armenian, Circassian, Slavonian, Albanian, Spanish, Italian, English, French, German, and Dutch, thus paving the way for studies of comparative literature. The book is conveniently concluded with elaborate indexes of fable characters, passages included, and numeration systems of other contributions in the field.